2009
DOI: 10.3141/2096-04
|View full text |Cite
|
Sign up to set email alerts
|

Safety Impact of Truck Lane Restrictions on Multilane Freeways

Abstract: Many states have implemented truck lane restrictions in an attempt to improve safety and mobility on freeways. These restrictions typically prohibit trucks from traveling in the median (left-most) lane of multi-lane highways; the restriction potentially increases passing opportunities and reduces negative interactions between slow-moving trucks and faster-moving vehicles. Virginia has restricted trucks from the median lane of some interstates with three or more lanes by direction since 1997, but no systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Large companies may have different work conditions and safety cultures than small companies. Other environmental factors may include road condition, traffic condition, hours‐of‐service regulations, and other relevant safety regulations [Kanazawa et al, ; Chen, ; Stigson et al, ; Fontaine et al, ; Hanowski et al, ; McKnight and Bahouth, ; Chen and Chen, ]. Effective prevention efforts should address these risk factors that are associated with drivers, vehicles, and environments.…”
Section: Discussionmentioning
confidence: 99%
“…Large companies may have different work conditions and safety cultures than small companies. Other environmental factors may include road condition, traffic condition, hours‐of‐service regulations, and other relevant safety regulations [Kanazawa et al, ; Chen, ; Stigson et al, ; Fontaine et al, ; Hanowski et al, ; McKnight and Bahouth, ; Chen and Chen, ]. Effective prevention efforts should address these risk factors that are associated with drivers, vehicles, and environments.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to measure the effectiveness of restricted lane use on motorways in the United States (Liu and 2007;Qi, 2009). There is evidence that truck-only lanes may negatively affect safety on motorways with a higher traffic volume (Fontaine et al, 2009). An analysis of Virginia's truck lane restriction showed that there is a breakpoint in safety performance at approximately 10 000 vehicles per day per lane.…”
Section: United Statesmentioning
confidence: 99%
“…Mannering et al reported that the truck-involved crash rate increased when trucks were restricted from the leftmost lane on an uphill freeway with three lanes in each direction, because the main cause of the crashes at that particular site was changing lanes to the right (17 ). Fontaine et al performed an empirical Bayes analysis to evaluate the safety impact of Virginia's truck lane restrictions by using 6 years of crash data from 22 sites with restrictions and 16 similar sites without restrictions (18). They stated that the safety performance was significantly affected by the traffic volume and that the restrictions likely played no role.…”
Section: Crash Analysis and Traffic Characteristicsmentioning
confidence: 99%